A comparative understanding of critical problems faced by Pakistani and Indian transportation industry - Hussain, Fawad; Saleh, Saleh Abduallah; Saud, Mohammad Basir; Md Isa, Mohd Azwardi (2015)
As As the beginning step of any developing nations towards their infrastructure development is to develop their roads and transport industry. Almost 1.1 billion populations share the travel and transportation industry in India.On the other hand, the Pakistan transportation industry is also extensive and elevating about 170 million users of transportation.Indian and Pakistani specifically within bus industry have good inter connectivity within and between the urban and rural areas as well as connectivity between the two countries, which is dramatically helping the economic alleviation of both countries.Due to high economic instability, unemployment and poverty rate are among the reasons why both the governments are very committed and seriously taken further action to help boost their economy.They believe that any form of transportation development would play a vital role in the development of land, infrastructure which could indirectly support many other industries' development, such as tourism, freighting and shipping businesses, just to mention a few. However, it seems that their previous transportation planning in the due course has failed to meet the fast growing demand. As with the spin of time, both the countries are looking forward for a reasonable, safe and economical long term solutions, which is from time to time keep appreciating and reacting according to other key economic drivers.Content analysis method and case study approach is used in this paper and secondary data from the bureau of statistic is used for case analysis.The paper centered on the mobility concerns of the lower and middle income people in India and Pakistan.The paper is aimed to highlight the weaknesses, opportunities and limitations resulting from low priority industry for government, which is making the either country's public suffer.The paper has concluded that the main issue is identified as the slow, inappropriate and unfavorable decisions which are not in favor of long term country's economic development and public welfare as well as interest.The paper also recommends to future market sense public and private transportation, which has failed to meet the public expectations.